Хірургічне лікування захворювань ендокринних органів (огляд діяльності кафедри та клініки факультетської хірургії Львівського національного медичного університету імені Данила Галицького за 1958-2008 рр.) - Павловський, М. П. (Clinical Endocrinology and Endocrine Surgery, 2008)
One of the main problem, the faculty surgery department of Lviv national medical university by Danylo Galytski is dealing with, beginning from it's foundation in 1897, is the surgery of endocrine organs. During all period of activity at department big attention was given to surgical treatment of endemic goiter, due to endemy of goiter in the western regions of Ukraine, combined management of different forms of thyroid cancer; surgeons in our department are working at improvement of early diagnosis of primary hyperparathyroidism. Conventional and endoscopic surgery is performed in our clinic in cases of adrenal tumors, neuroendocrine tumors of pancreas, ovaries.